Microstructural Changes in Compressed Nerve Roots Are Consistent With Clinical Symptoms and Symptom Duration in Patients With Lumbar Disc Herniation. Issue 11 (June 2016) - Wu, Weifei; Liang, Jie; Ru, Neng; Zhou, Caisheng; Chen, Jianfeng; Wu, Yongde; Yang, Zong
Abstract : Study Design: A prospective study. Objective: To investigate the association between microstructural nerve roots changes on diffusion tensor imaging (DTI) and clinical symptoms and their duration in patients with lumbar disc herniation. Summary of Background Data: The ability to identify microstructural properties of the nervous system with DTI has been demonstrated in many studies. However, there are no data regarding the association between microstructural changes evaluated using DTI and symptoms assessed with the Oswestry Disability Index (ODI) and their duration. Methods: Forty consecutive patients with foraminal disc herniation affecting unilateral sacral 1 (S1) nerve roots were enrolled in this study. DTI with tractography was performed on the S1 nerve roots. Clinical symptoms were evaluated using an ODI questionnaire for each patient, and the duration of clinical symptoms was noted based on the earliest instance of leg pain and numbness. Mean fractional anisotropy (FA) and apparent diffusion coefficient (ADC) values were calculated from tractography images. Results: The mean FA value of the compressed lumbar nerve roots was significantly lower than the FA of the contralateral nerve roots ( P < 0.001). No notable difference in ADC was observed between compressed nerve roots and contralateral nerve roots ( P = 0.517). In the compressed nerve roots, a significant negative association was observed between FA values and ODI and symptom duration. However, an obvious positive association was observed between ODI and ADC values and duration on the compressed side. Conclusion: Significant changes in diffusion parameters were found in the compressed sacral nerves in patients with lumbar disc herniation and leg pain, indicating that the microstructure of the nerve root has been damaged. Level of Evidence: 3